2018
DOI: 10.1002/jnr.24229
|View full text |Cite
|
Sign up to set email alerts
|

Altered fecal microbiota composition in all male aggressor‐exposed rodent model simulating features of post‐traumatic stress disorder

Abstract: The bidirectional role of gut-brain axis that integrates the gut and central nervous system activities has recently been investigated. We studied "cage-within-cage resident-intruder" all-male model, where subject male mice (C57BL/6J) are exposed to aggressor mice (SJL albino), and gut microbiota-derived metabolites were identified in plasma after 10 days of exposure. We assessed 16S ribosomal RNA gene from fecal samples collected daily from these mice during the 10-day study. Alpha diversity using Chao indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 71 publications
5
44
0
Order By: Relevance
“…Differential abundance analysis of individual taxa revealed multiple bacterial taxa that were increased or decreased in the sleep-disrupted group compared to controls, including an increase in the Firmicutes:Bacteroidetes (F:B) ratio and a decrease in Lactobacillus, Actinobacteria, and Bifidobacterium, all of which have established physiological impacts. An increase in the F:B ratio is a blunt measure of community shift and has been seen in many pathological states including obesity [55,56], chronic stress [57], as well as an acute short sleep paradigm in humans [14] and a chronic sleep fragmentation paradigm in rodents [16]. The phylum Actinobacteria, genus Bifidobacterium, and genus Lactobacillus were all low in sleep-disrupted mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential abundance analysis of individual taxa revealed multiple bacterial taxa that were increased or decreased in the sleep-disrupted group compared to controls, including an increase in the Firmicutes:Bacteroidetes (F:B) ratio and a decrease in Lactobacillus, Actinobacteria, and Bifidobacterium, all of which have established physiological impacts. An increase in the F:B ratio is a blunt measure of community shift and has been seen in many pathological states including obesity [55,56], chronic stress [57], as well as an acute short sleep paradigm in humans [14] and a chronic sleep fragmentation paradigm in rodents [16]. The phylum Actinobacteria, genus Bifidobacterium, and genus Lactobacillus were all low in sleep-disrupted mice.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the two most prevalent phyla in the mammalian gut, the Firmicutes:Bacteroidetes (F:B) ratio, is a blunt measure of community shift. An increase in the F:B ratio has been seen in obesity [55,56], stress [57], as well as models of acute [14] and chronic [16] sleep disruption. We found a significant sleep disruption-induced increase in the F:B ratio (Fig 4B) that was significant at R2 but not at R4.…”
Section: Multiple Bacterial Taxa Are Differentially Abundant In the Smentioning
confidence: 99%
“…Since the HPA axis is deeply rooted in vertebrate phylogeny [57], similar rebalancing of digesta versus mucin glycan energy channels in response to stressors experienced by the host could be a conserved mechanism by which vertebrates regulate their microbiomes. Trade-offs between mucin glycan and digesta metabolizing bacteria are reported in laboratory mice exposed to chronic stressors [67][68][69], HIV patients experiencing mucosal barrier disruption [70], fasting vertebrates [71,72] and mammals undergoing torpor or hibernation [73][74][75][76][77]. Although these studies typically discuss the bacterial patterns observed within the context of diet or specific stressors, homologous HPA axis responses across these biological groups might provide an alternate or complimentary mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…9 In animal models, PTSD is linked with differences in gut microbial composition, which can, in turn, modulate aggressive behavior and exert a negative influence on the mice that suffer because of this aggression. 10,11 Moreover, these changes can be transmitted by fecal transplant in rodent models, setting the stage for gut microbial modulation as an important avenue in PTSD. 10,11 Human studies are currently lacking in veterans with PTSD; however, patients with noncombat PTSD show altered gut microbial composition compared with those exposed to similar trauma but who did not develop PTSD.…”
Section: Focus Group 2: Liver Diseasesmentioning
confidence: 99%
“…10,11 Moreover, these changes can be transmitted by fecal transplant in rodent models, setting the stage for gut microbial modulation as an important avenue in PTSD. 10,11 Human studies are currently lacking in veterans with PTSD; however, patients with noncombat PTSD show altered gut microbial composition compared with those exposed to similar trauma but who did not develop PTSD. 12,13 The interaction between PTSD, depression and the onset of liver disease in veterans is a relevant question since several lifestyle-associated disorders can propagate liver disease.…”
Section: Focus Group 2: Liver Diseasesmentioning
confidence: 99%